Faktor Penyebab dan Dampak Negatif Nikah Siri Bagi Perempuan (Studi Kasus: Kampung Pandean, Kelurahan Ngadirejo, Kecamatan Kartasura, Kabupaten Sukoharjo Tahun 2015) - Saitian, Supuh, Dra. Hj. Sri Arfiah, S.H., M.Pd (2015)
This study aimed to describe the series of Marriage Causes for Women, Nikahsiri Negative Impact for Women. The background of this research is in the village Pandean, Ngadirejo villages, districts kartusuro, Sukoharjo. Data collection techniques using observation, interview techniques, and documentation. The results showed that the Causes and Effects of Negative NikahSiri for Women are economic factors, the religious factor, the factor of bond, lack of awareness of the law while the impact on the child is not inherited from the father and not going to school because the child's birth certificate does not exist. Practice nikahsiri is still a social phenomenon that is fairly widespread and is still a debate in the public arena. Validity of the data using two kinds of triangulation, the triangulation of data sources and triangulation techniques or methods of data collection. The research uses an interactive model of data analysis techniques through a process of data collection, data reduction, data presentation, and conclusion. Results of this study can be concluded that describe Causes and negative effects of marriage siri for Women, in the village Pandean villages Ngadirejo Kartasura Sukoharjo districts, marriage siri have a positive impact and a negative impact on the husband, wife, and children. The downside experienced women (wives) and children than that experienced by the husband. Marriage siri many negative impacts on women (wives) and children, when the husband was not responsible. The Government needs to socialize constantly about the negative impact of unofficial marriages, the government needs to provide strict sanctions for perpetrators nikahsiri irresponsible and those who have helped the nikahsiri.